Unique chicken B cell development: species-specific mechanisms and contradictory requirements of B cell receptor for post-hatched B cell development - Woo, Seung Je; Songodan, Thirubasyini; Han, Jae Yong (Frontiers in Immunology, 2026)
Chicken B cell development represents a remarkable evolutionary divergence from mammalian paradigms, featuring unique three-stage ontogeny centered on the bursa of Fabricius, an avian-specific primary B cell lymphoid organ. Unlike mammals where B cells develop continuously in bone marrow, chickens utilize a temporally restricted program spanning pre-bursal (E5-E14), bursal (E8-hatching), and post-bursal phases (hatching-bursal involution), each characterized by distinct molecular mechanisms and anatomical sites. In this review, we documented chicken B cell development in three developmental phases (pre-bursal to post-bursal phases) and compared it with mammalian B cell development mostly in humans as a representative mammalian model. In chicken, while the embryonic bursa of Fabricius serves as the primary B cell receptor (BCR)-dependent B cell developmental organ, it also supports BCR-independent early colonization followed by extensive activation-induced cytidine deaminase (AID)-mediated gene conversion rather than V(D)J recombination for antibody diversification. Recent gene knockout studies reveal paradoxical BCR signaling requirements for post-hatched chicken B cell development, with JH knockout chickens lacking post-hatched B cells, while recombination activating gene 1 (RAG1) knockout chickens maintain post-hatched bursal B cell populations through alternative pathways. Single-cell RNA sequencing has identified previously unrecognized chicken B cell subpopulations and provided molecular signatures for bursal and post-bursal B cells, addressing longstanding phenotypic marker limitations. These findings demonstrate that effective chicken humoral immunity can be achieved through alternative evolutionary strategies, with reduced dependence on RAG1 activity compared to mammalian systems, providing new perspectives on immune system evolution and adaptive immunity mechanisms.